Challenges in the promotion of research in Brazil in the perspective of the National Scientific And Technological Development Council (Research, Society and Development, 2022)
The present study aimed to identify the challenges in promoting research in Brazil from the perspective of the National Council for Scientific and Technological Development - CNPq. From a methodological point of view, this is a descriptive and exploratory study, of a documentary nature, based on the analysis of data from the annual report of accountability of the CNPq management, fiscal year 2016, using Bardin's content analysis technique. The results found revealed a limitation of budgetary and financial resources (both to honor assumed commitments and to launch innovative actions); insufficient number of civil servants in view of institutional responsibilities and challenges (situation worsened by the growing number of retirements); political and administrative changes. In view of this, it is concluded that there is a gap in financial and human resources aimed at research, which compromises the evolution of science. This fall has been happening gradually and continuously with no prospects of change for growth.